A Synthetic Route to the MT1-MMP Inhibitor Ancorinoside D - Petermichl, Markus; Steinert, Christine; Schobert, Rainer (Synthesis, 2019)
A methyl ester of ancorinoside D, a 3-acyltetramic acid metabolite of a sponge Penares sollasi, was synthesised in ten steps starting from a protected β-d-glucopyranosyl-(1→4)-d-galactopyranosyltrichloroacetimidate donor. Its attachment to the left half of the 3-acyl spacer by a Schmidt glycosylation, 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-mediated oxidation to the uronic acid, introduction of the Z-alkene via Wittig reaction, and functionalisation of the spacer terminus with Meldrum’s acid gave a β-keto ester that reacted with dimethyl N-methyl-d-aspartate under neutral conditions to afford a fully protected ancorinoside D as the product of an unusual domino N-acylation–Dieckmann condensation. Global deprotection left a methyl ester of ancorinoside D, which resisted all saponification attempts.
Keywords: tetramic acid; Wittig reaction; Dieckmann cyclisation; natural products; glycosylation; ancorinoside; MMP inhibitor; domino reaction